2020
DOI: 10.1007/s00259-020-04777-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of PSMA-guided radiotherapy for patients with oligorecurrent prostate cancer

Abstract: Purpose First-line treatment of patients with recurrent, metastatic prostate cancer involves hormone therapy with or without additional systemic therapies. Prostate-specific membrane antigen (PSMA) positron emission tomography (PET)/computed tomography (CT) allows the detection of oligometastatic disease that may be amenable to image-guided radiotherapy. The current study classifies the type and localization of metastases and the clinical outcome of PSMA-PET/CT-guided radiotherapy to selected meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…Koerber et al retrospectively included 86 patients with oligometastatic relapse (≤5 lesions detected by PSMA PET/CT) and treated them with RT ± ADT. They showed higher BR-FS rates at 2 and 3 years (85.1% and 55.1%, respectively) than those in our study [ 46 ]. However, their study included a greater proportion of patients receiving concomitant ADT, which may explain this difference.…”
Section: Discussioncontrasting
confidence: 70%
“…Koerber et al retrospectively included 86 patients with oligometastatic relapse (≤5 lesions detected by PSMA PET/CT) and treated them with RT ± ADT. They showed higher BR-FS rates at 2 and 3 years (85.1% and 55.1%, respectively) than those in our study [ 46 ]. However, their study included a greater proportion of patients receiving concomitant ADT, which may explain this difference.…”
Section: Discussioncontrasting
confidence: 70%
“…Prior studies have shown a change in intended or actual management in between a third to two-thirds of patients [11][12][13][14]. Multiple further studies assessed the impact of PET on patient outcome [15][16][17][18][19][20][21][22]. A prior prospective study documented a PSA response of >50% in nearly 3 of 4 patients (63 of 86; 73.3%), much like the results from our registry, and the 3-year biochemical free survival was 55% [15].…”
Section: Discussionsupporting
confidence: 53%
“…PSMA-guided treatment of single-lesion or oligometastatic relapse is being increasingly applied and may achieve favorable outcomes [109][110][111][112]. In this context, improved accuracy in detecting such lesions may result in superior progression-free survival after targeted treatment.…”
Section: Prostate Cancermentioning
confidence: 99%